A Framework for Automatic Lecturer's Attendance System Using Automated Vehicle Identification (AVI) Technology - Shafter, Emammer Khamis (2006)
Automatic Vehicle Identification (AVI) technology can be used to significantly improve the efficiency of lecturer's attendance system by providing the capability of automatic identification and data capture. This technology poses many new challenges on current data management systems. AVI data are time-dependent, dynamically changing, in large volumes, and carry implicit semantics. Radio frequency identification (RFID) data management systems need to effectively support such large scale temporal data created by RFID applications. These systems need to have an explicit temporal data model for RFID data to support tracking and monitoring attendance. In addition, the university needs to have an automatic method to transport data from AVI reader to database. This research proposed a framework for Automatic lecturer's Attendance system using AVI technology. A prototype has been developed to test the framework.